Association of plasma bone morphogenetic protein‐4 levels with arterial stiffness in hypertensive patients. Issue 11 (27th October 2022) - Wang, Ning; Guo, Ying; Dong, Ying; Li, Xueting; Liu, Qian; Liu, Qi; Wang, Guohong; Qin, Mingzhao; Zhang, Zhenzhou; Song, Jiawei; Liang, Lirong; Zhong, Jiuchang
Abstract: Background: Arterial stiffness interacts with hypertension, becoming an early marker of hypertension‐mediated target organ damage. This study aimed to assess the association between plasma concentrations of bone morphogenetic protein‐4 (BMP‐4) and arterial stiffness during hypertension. Methods: Using cardio‐ankle vascular index (CAVI) to determine arterial stiffness status, 204 individuals with essential hypertension were classified into two groups, high CAVI (abnormal) group ( n  = 94) and low (normal) CAVI group ( n  = 110). Data were collected including clinical characteristics and laboratory measurements. Plasma levels of BMP‐4 were tested by using ELISA analysis. Results: Plasma levels of BMP‐4 were substantially greater in high CAVI group than that in low CAVI group [38.51 (31.79–50.83) pg/mL vs. 31.15 (29.38–32.37) pg/mL; p  < 0.001]. As shown by spearman correlation analysis, BMP‐4 concentrations were correlated with CAVI values in hypertensive individuals ( r  = 0.406, p  < 0.001). After adjustment for potential confounders, elevated BMP‐4 levels were related with high CAVI (OR, 1.070; 95% CI, 1.003–1.108; p  < 0.001). The best BMP‐4 cutoff value for identifying high CAVI, as determined by ROC curve analysis, was 33.34 pg/mL (AUC, 0.751; 95% CI, 0.683–0.818; p  < 0.001). Conclusion: Plasma levels of BMP‐4 are increased in hypertensive individuals with high CAVI. Elevated BMP‐4 levels are strongly correlated with higher CAVI values, implying a predictive value of BMP‐4 in arterial stiffness during hypertension. Abstract : Arterial stiffness can interact with hypertension, thereby becoming an early marker of hypertension‐mediated targeted organ damage. Plasma levels of BMP‐4 have the ability to identify increased arterial stiffness in patients with hypertension. CAVI, cardio‐ankle vascular index; BMP‐4, bone morphogenetic protein‐4.